Non-canonical extracellular complement pathways and the complosome paradigm in cancer: a scoping review - de Freitas Oliveira-Tore, Camila; de Moraes, Amarilis Giaretta; Plácido, Helena Musetti B. S.; Signorini, Nathalia M. D. L.; Fontana, Pamela Dias; da Piedade Batista Godoy, Tatiane; Boldt, Angelica Beate Winter; de Messias, Iara (Frontiers in Immunology, 2025)
The Complement System (CS) comprises three catalytic pathways that can be activated by specific immune triggers. However, within the tumor microenvironment (TME), CS intracellular components, recently named as complosome, play roles that extend beyond the activation and regulation of its pathways. The interaction between TME elements and tumor cells alters the local immune response, leading to inflammation, cell proliferation, and tumor invasion. Our focus is on understanding the significance of complosome and non-canonical pathways in cancer. In this scoping review, we analyzed 45 articles that discussed the various roles of CS components in carcinogenesis. Many CS components, including C1q, C3a-C3aR, C5a-C5aR, factor H, and properdin, some of them at the intracellular level, may play a dual role in tumor progression, demonstrating either anti-tumor or pro-tumor activity independent of complement pathway activation. The specific function of each component can influence both the type and stage of tumor cells. There is a notable lack of studies on the role of the lectin pathway in tumor development, and this knowledge gap must be addressed to fully understand the role of complosome in cancer. Nevertheless, the activation of CS and the roles of its components in complosome pathways are crucial steps in tumor development.